Sequential Simulations of Steel Frame Buildings Under Multi-Phase Hazardous Loads During Earthquake and Tsunami - Isobe, Daigoro; Tanaka, Seizo (Frontiers in Built Environment, 2021)
Based on the experience of the 2011 Great East Japan Earthquake and the following tsunami, this study aims to comprehensively seek an effective building design that can withstand multi-phase hazardous loads by conducting two kinds of simulations. First, a structural collapse analysis of a steel frame building under successive applications of varying loads was performed using the ASI-Gauss code. The steel frame building model was first excited under an acceleration record observed in Kesennuma-shi during the earthquake, and then fluid forces due to a tsunami wave were applied. Then, the collapse behavior of the building was investigated by colliding a debris model with the building model. The impact conditions on the surface of the building (flow velocity, inundation height, and posture of debris) showed strong relations to the maximum story drift angle. Subsequently, a fluid analysis was conducted on an actual tsunami evacuation building with openings, using the stabilized finite element method based on the volume of fluid method. The aim was to compare the obtained wave force with an estimated one to verify the practicability of the latter when applied to a building with openings. Finally, a sequential structural analysis, with a debris collision phase at the end, was conducted using the ASI-Gauss code to simulate the washout behavior of the building.